The man made of smoke : a novel - North, Alex, 1976- (Celadon Books, 2025)
"The latest gripping serial killer thriller from the New York Times bestselling author Alex North. Dan Garvie's life has been haunted by the crime he witnessed as a child-narrowly escaping an encounter with a notorious serial killer. He has dedicated his life since to becoming a criminal profiler, eager to seek justice for innocent victims. So when his father passes away under suspicious circumstances, Dan revisits his small island community, determined to uncover the truth about his death. Is it possible that the monster he remembers from his childhood nightmares has returned after all these years? With his signature shock and suspense, Alex North brings us The Man Made of Smoke. In turn emotional, introspective, and utterly terrifying, this is a story of fathers and sons, shadows and secrets, and the fight we all face to escape the trauma of the past"--